Csf1 Signaling Regulates Maintenance of Resident Macrophages and Bone Formation in the Mouse Cochlea - Okano, Takayuki; Kishimoto, Ippei (Frontiers in Neurology, 2019)
In the mammalian cochlea, resident macrophages settle in the spiral ligament, spiral ganglion, and stria vascularis even in the steady state condition. The resident macrophages in the cochlea are believed to maintain homeostasis in the inner ear and become active on the front line of defense following inner ear damage. However, the exact roles of cochlear resident macrophages require further clarification. Colony stimulating factor-1 (Csf1) signaling regulates the survival, proliferation, and differentiation of resident macrophages and appears to be essential for resident macrophages in the inner ear. To examine the roles of Csf1 signaling in auditory function, we studied phenotypes of the ossicles and inner ear of homozygous Csf1 mutant (op/op) mice. The ossicles including the incus and stapes of Csf1op/op mice macroscopically demonstrated bone thickening, and the otic capsules of the inner ear of Csf1op/op mice were also thick and opaque. Histological analyses demonstrated that the otic capsules of Csf1op/op mice were thickened and showed spongy bone degeneration. Measurements of the auditory brainstem response (ABR) revealed significant elevation of thresholds in Csf1op/op mice at four weeks old compared with wild-type littermates, indicating that Csf1op/op mice demonstrate hearing loss due to, at least in part, deformity of the ossicles and bone capsule of the inner ear. Furthermore, Csf1op/op mice possess significant deficiencies in the number of resident macrophages in the spiral ligament and stria vascularis, but not in the spiral ganglion. These data provide evidence that Csf1 signaling plays important roles not only in bone formation in the inner ear, but also in the maintenance of resident macrophages in the spiral ligament and stria vascularis of the adult mouse cochlea.